2017
DOI: 10.1016/j.neubiorev.2017.04.011
|View full text |Cite
|
Sign up to set email alerts
|

The effect of active video games on cognitive functioning in clinical and non-clinical populations: A meta-analysis of randomized controlled trials

Abstract: Physically-active video games ('exergames') have recently gained popularity for leisure and entertainment purposes. Using exergames to combine physical activity and cognitively-demanding tasks may offer a novel strategy to improve cognitive functioning. Therefore, this systematic review and meta-analysis was performed to establish effects of exergames on overall cognition and specific cognitive domains in clinical and non-clinical populations. We identified 17 eligible RCTs with cognitive outcome data for 926 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
232
14
12

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 311 publications
(298 citation statements)
references
References 50 publications
20
232
14
12
Order By: Relevance
“…27 Meta-analyses of studies on action video gaming effects in healthy subjects and clinically impaired populations reveal a small to medium effect size on a series of cognitive skills. 28,29 However, when considering only patients with neurological conditions, exergames are equally effective for global cognitive functions and attention, and more effective for executive functions and visuo-spatial perception, compared with conventional therapies. 29 Apart from promising results in motor functions, 24 there is increasing evidence showing that motor exergames may prove beneficial in cognitive rehabilitation, 28 thus raising the hope that improved performance in a motor function may be beneficial for other untrained functional domains.…”
Section: Exergames In Motor Neurorehabilitation For Pwmsmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Meta-analyses of studies on action video gaming effects in healthy subjects and clinically impaired populations reveal a small to medium effect size on a series of cognitive skills. 28,29 However, when considering only patients with neurological conditions, exergames are equally effective for global cognitive functions and attention, and more effective for executive functions and visuo-spatial perception, compared with conventional therapies. 29 Apart from promising results in motor functions, 24 there is increasing evidence showing that motor exergames may prove beneficial in cognitive rehabilitation, 28 thus raising the hope that improved performance in a motor function may be beneficial for other untrained functional domains.…”
Section: Exergames In Motor Neurorehabilitation For Pwmsmentioning
confidence: 99%
“…28,29 However, when considering only patients with neurological conditions, exergames are equally effective for global cognitive functions and attention, and more effective for executive functions and visuo-spatial perception, compared with conventional therapies. 29 Apart from promising results in motor functions, 24 there is increasing evidence showing that motor exergames may prove beneficial in cognitive rehabilitation, 28 thus raising the hope that improved performance in a motor function may be beneficial for other untrained functional domains. 29 The effect of exergames (balance board video game) on sustained attention was investigated in a small crossover study on 21 pwMS.…”
Section: Exergames In Motor Neurorehabilitation For Pwmsmentioning
confidence: 99%
“…Most studies involving exergames investigated the acute and chronic effects on caloric expenditure (Barkman et al, 2016), motor aspects (Collado-Mateo et al, 2017), and cognitive function (Garcia et al, 2016; Stanmore et al, 2017) in different healthy and clinical populations (Dos Santos Mendes et al, 2012; Collado-Mateo et al, 2017). However, less is known about the physiological responses during an exergame session, especially regarding oxygen uptake () and heart rate (HR).…”
Section: Introductionmentioning
confidence: 99%
“…Donker et al (2013) indicated that mental health apps have the potential to improve health outcomes and treatment accessibility. A meta-analytic review by Stanmore et al (2017) also showed that telehealth, such as videogames, not only improved the participant's global cognition score, but also enhanced their cognitive functioning, which is very often affected by depression. Although other health outcomes related to depression were not the focus of this review, reviewed studies showed an inconsistency in findings regarding the positive effect of telehealth interventions.…”
Section: Discussionmentioning
confidence: 97%
“…Several systematic reviews and meta-analyses have examined technology-based interventions for depression (Agboola et al 2015;Davies et al 2014;Garc ıa-Lizana & Muñoz-Mayorga 2010;Paganini et al 2018;Stanmore et al 2017;Strauss et al 2014). However, only a few reviews attempted to synthesize data to determine the level of acceptability and the influencers on the implementation of telehealth.…”
mentioning
confidence: 99%